Telaah Kekinian Kotbah Topikal dari Perspektif Aliran Pentakosta - Tambunan, Rexi; Andrianti, Sarah (Pusat Studi Pentakosta Indonesia, 2021)
This study aims to explain the perspective of the Pentecostal church on topical preaching. Preaching is the delivery of God's message to the congregation through people who have been chosen by God. The research method used in this study is qualitative using a descriptive approach and literature review. Various types of preaching models are used by preachers. One of the most popular types of sermons is topical preaching. Because in the perspective of the Pentecostal church, it is known that there is no prohibition regarding the way someone delivers a sermon. The most important thing is to use the Bible as a basis for preaching. Based on the results of the discussion, the Pentecostal church interprets topical sermons as a way of delivering the content of the Bible that is relevant and contextual to the daily life of the congregation. Without reducing the essence and authority of God's word. Because God does not limit the way humans can preach or convey God's words. The preachers of the Pentecostal church believe that the Holy Spirit will guide the preacher to be able to prepare and deliver a sermon so that it is right on target.Penelitian ini bertujuan untuk menjelaskan perspektif gereja aliran Pentakosta terhadap khotbah topikal. Khotbah merupakan penyampaian pesan Allah kepada jemaat melalui orang-orang yang telah dipilih oleh Allah. Metode penelitian yang digunakan dalam penelitian ini adalah kualitatif dengan menggunakan pendekatan deskriptif dan kajian literatur. Berbagai jenis model kotbah dipakai oleh para pengkotbah. Salah satu jenis kotbah yang banyak disukai adalah kotbah topikal. Karena dalam perspektif gereja beraliran pentakosta diketahui tidak ada larangan terkait cara seseorang dalam menyampaikan khotbah. Yang terpenting adalah harus menggunakan Alkitab sebagai landasan dalam berkhotbah. Berdasarkan hasil pembahasan, gereja aliran Pentakosta memaknai kotbah topikal sebagai salah satu cara penyampaian isi Alkitab yang relevan serta kontekstual dengan kehidupan jemaat sehari-hari.Tanpa mengurangi esensidan otoritas firman Allah.Karena Tuhan tidak membatasi cara manusia dalam berkhotbah atau menyampaikan firman Tuhan.Para pengkotbah gereja Pentakosta percaya bahwa Roh Kudus akan menuntun pengkotbah untuk dapat mempersiapkan dan menyampaikan kotbah sehingga tepat pada sasaran.